2010
DOI: 10.1182/blood.v116.21.3703.3703
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia After Cardiopulmonary Bypass Surgery.

Abstract: 3703 Introduction: Heparin induced thrombocytopenia (HIT) has been reported to occur in up to 3% patients undergoing Cardiopulmonary Bypass (CPB) surgery by using clinical criteria. However, the accurate diagnosis of HIT in this setting is very difficult due to underlying thrombocytopenia related to the mechanical consumption of platelets by the bypass machine. This study aims to evaluate (1) the clinical and laboratory characteristics of thrombocytopenia aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Some studies reported that the incidence of thrombocytopenia was lower in patients in the ICU. 12,13 Vanderschueren et al 14 reported thrombocytopenia in 41.3% of (136/329) adult patients in the ICU. Chandra et al reported that 31.5% (142/450) of patients had thrombocytopenia after CABG, and in the study by Tanriverdi et al thrombocytopenia was found in 38.3% (64/167) of patients after cardiovascular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that the incidence of thrombocytopenia was lower in patients in the ICU. 12,13 Vanderschueren et al 14 reported thrombocytopenia in 41.3% of (136/329) adult patients in the ICU. Chandra et al reported that 31.5% (142/450) of patients had thrombocytopenia after CABG, and in the study by Tanriverdi et al thrombocytopenia was found in 38.3% (64/167) of patients after cardiovascular surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 14 We had a high proportion of patients who underwent cardiopulmonary bypass, had sepsis, and were on ECMO, all of which impact the incidence of thrombocytopenia in our patient population, driving higher 4T scores and potentially leading to the inappropriate ordering of PF4 tests. 15 , 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…This may reflect the fact that thrombocytopenia can occur in up to 55% of patients with renal dysfunction, making the diagnosis of HIT and the use of the 4T score challenging in this patient population 4,14 . We had a high proportion of patients who underwent cardiopulmonary bypass, had sepsis, and were on ECMO, all of which impact the incidence of thrombocytopenia in our patient population, driving higher 4T scores and potentially leading to the inappropriate ordering of PF4 tests 15–17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The incidence of postoperative thrombocytopenia following CABG has been reported to range from 10 to 32%. 7,8 Recent evidence suggests this thrombocytopenia may be paradoxically indicative of increased platelet thrombogenicity and a postoperative thrombotic state. In a study of 6,130 adult post-CABG patients, those with moderate to severe thrombocytopenia (platelet count < 100 Â 10 9 /L) had a significantly higher risk of stroke between 2 and 30 days following the procedure.…”
Section: Introductionmentioning
confidence: 99%